2021
DOI: 10.1073/pnas.2023909118
|View full text |Cite
|
Sign up to set email alerts
|

SLC-30A9 is required for Zn 2+ homeostasis, Zn 2+ mobilization, and mitochondrial health

Abstract: The trace element zinc is essential for many aspects of physiology. The mitochondrion is a major Zn2+ store, and excessive mitochondrial Zn2+ is linked to neurodegeneration. How mitochondria maintain their Zn2+ homeostasis is unknown. Here, we find that the SLC-30A9 transporter localizes on mitochondria and is required for export of Zn2+ from mitochondria in both Caenorhabditis elegans and human cells. Loss of slc-30a9 leads to elevated Zn2+ levels in mitochondria, a severely swollen mitochondrial matrix in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Similarly, the role of SLC-30A9 in Zn 2+ export from mitochondria was also confirmed in humans, where loss of SLC-30A9 leads to excessive Zn 2+ accumulation in mitochondria, severe mitochondrial swelling, increased ROS production and dysregulated metabolic function. Additionally, it was proposed that SLC-30A9 is crucial for sperm activation and organismal fertility, and in neurons, the SLC-30A9 mutation is responsible for Birk-Landau-Perez cerebrorenal syndrome-an autosomal recessive syndrome, characterized by nephropathy, muscle weakness, intellectual disability, camptocormia and oculomotor apraxia [30,31].…”
Section: Zn 2+ In Mitochondrial Homeostasismentioning
confidence: 99%
“…Similarly, the role of SLC-30A9 in Zn 2+ export from mitochondria was also confirmed in humans, where loss of SLC-30A9 leads to excessive Zn 2+ accumulation in mitochondria, severe mitochondrial swelling, increased ROS production and dysregulated metabolic function. Additionally, it was proposed that SLC-30A9 is crucial for sperm activation and organismal fertility, and in neurons, the SLC-30A9 mutation is responsible for Birk-Landau-Perez cerebrorenal syndrome-an autosomal recessive syndrome, characterized by nephropathy, muscle weakness, intellectual disability, camptocormia and oculomotor apraxia [30,31].…”
Section: Zn 2+ In Mitochondrial Homeostasismentioning
confidence: 99%
“…In the mitochondrial matrix, ZnT9-50Val-transfected cells had a higher zinc content in basal conditions as well but that was not further affected by incubating with 100 µM zinc, contrary to cells overexpressing ZnT9-50Met, or an empty vector (Figure 4G). Given that mitochondrial zinc content is reported to depend on ER zinc transport ( 21, 22 ), similar experiments were carried out, but this time blocking the ER zinc exporter ZIP7 for 30 min to accumulate zinc in this organelle. The result was an increase of zinc levels in the mitochondrial matrix of control cells but not in ZnT9 overexpressing cells (Supplementary Material, Figure S8B).…”
Section: Resultsmentioning
confidence: 99%
“…We then used super-resolution STED microscopy to confirm the presence of ZnT9 in mitochondria as described by others ( 21, 22 ) (Figure 3). ZnT9-HA was co-stained with anti-TOM20 (Figure 3A), a mitochondrial outer membrane resident protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, HUEL-ZnT9 was also named GAC63 for GRIP1-associated coactivator 63. However, more recent studies, employing computational and loss of function analyses, have found a preponderant role of ZnT9 in the regulation of mitochondrial Zn homeostasis, which is conserved throughout evolution [335,336].…”
Section: Znt8 (Slc30a8)mentioning
confidence: 99%